Penerapan Metode Forward Chaining Untuk Mendeteksi Perbedaan Print Digital Dan Sablon - Imannudin Imannudin Imannudin; Mohamad Endra Gunawan; Diki Gunawan Gunawan; Hariyani Febrianty Febrianty; Adelia Anjani Anjani; Munawaroh Munawaroh Munawaroh (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2021)
Screen printing is a design pattern that can be painted, cut, or cut according to the example. At this time the use of digital printing techniques is being loved and is starting to be widely used and applied in various things. With these two methods, there is a difference in price and print results between screen printing and digital printing. Both methods have their respective advantages and disadvantages. Therefore, it is necessary to compare and see the difference between screen printing and digital printing. The purpose of this research is to see the differences as well as the advantages and disadvantages between digital printing and screen printing. The method used in this research is the Forward Chaining method. The Forward Chaining method is a search method or forward tracking technique that starts with existing information and combines rules to produce a conclusion or goal.